Factors Associated With Patient's Refusal of Recommended Cancer Surgery: Based on Surveillance, Epidemiology, and End Results - Hu, Xianglin; Ye, Hui; Yan, Wangjun; Sun, Yangbai (Frontiers in Public Health, 2022)
Objectives: Most non-metastatic cancer patients can harvest a preferable survival after surgical treatment, however, patients sometimes refuse the recommended cancer-directed surgery. It is necessary to uncover the factors associated with patent’s decision in taking cancer surgery and explore racial/ethnic disparities in surgery refusal. Methods: Based on the Surveillance, Epidemiology and End Results (SEER)-18 program, we extracted data of non-metastatic cancer patients who didn’t undergo surgery. Ten common solid cancers were selected. Four racial/ethnic categories were included: White, black, Hispanic, and Asian/Pacific Islander (API). Primary outcome was patient’s refusal of surgery. Multivariable logistic regression models were used, with reported odds ratio (OR) and 95% confidence interval (CI). Results: Among 318318 patients, the incidence of surgery refusal was 3.5%. Advanced age, female patients, earlier cancer stage, uninsured/Medicaid and unmarried patients were significantly associated with higher odds of surgery refusal. Black and API patients were more likely to refuse recommended surgery than white patients in overall cancer (black-white: adjusted OR, 1.18; 95% CI, 1.11-1.26; API-white: adjusted OR, 1.56; 95% CI, 1.41-1.72); those racial/ethnic disparities narrowed down after additionally adjusting for insurance type and marital status. In subgroup analysis, API-white disparities in surgery refusal widely existed in prostate, lung/bronchus, liver, and stomach cancers. Conclusions: Patient’s socioeconomic conditions reflected by insurance type and marital status may play a key role in racial/ethnic disparities in surgery refusal. Oncological surgeons should fully consider the barriers behind patient’s refusal of recommended surgery, thus promoting patient-doctor shared decision-making and guiding patients to the most appropriate therapy.